Enzyme-mediated oxidative dimerization reactions of cyano-resveratrol analogues. Issue 47 (21st November 2019) - Shao, Zhibo; Kang, Xiaodong; Li, Hongpeng; Ran, Lu; Li, Wenling
Graphical abstract: Highlights: Two substituted 2, 3-diaryl acrylonitrile derivatives were prepared. Two different cyano-oligostilbenes were firstly synthesized. The oxidative coupling reactions of olefin-substituted stilbenes were explored. The cyano groups of resveratrol analogues had no influence on the biomimetic oxidations. Abstract: The synthesis and oxidative coupling reactions of two cyano-resveratrol analogues were studied. An 8-5-coupled dihydrobenzofuran-type dimer and an 8-8-coupled diastereoisomeric indane mixture were prepared. The cyano groups of the resveratrol analogues had almost no influence on the regio- or stereoselectivity of the coupling reactions of the two precursors.